Developing the contextual framework of street arts project in preserving the Malaysian culture - Salau, Jimmy; Lee Abdullah, Qistina Donna; Salmiah, Abdul Hamid (Universiti Malaysia Terengganu, 2017)
Malaysia has unique and distinct culture, with a multi-racial population that brings diversity to the cultural facet of the country. Therefore, Malaysian culture should be maintained to prevent extinction. Preserving the culture and heritage is vital in the development of the modern world. Notwithstanding the increasing attention on technology advancement at the global level, the preservation of culture and heritage of local impacts points towards a prime role for regional tourism industry. This paper presents a conceptual framework that describes the street arts projects in Malaysia. It addresses the following key independent variables such as cultural content and audiences; moderator variables such as guidelines and demographic factors; and dependent variables such as city image and tourist expectations. The aim of this paper is to analyse and create new set of guidelines for Street Arts Project to preserve the Malaysian culture in the tourism sector. Through preliminary research, the main problems have been identified such as limited study on cultural and themes of street arts. From this paper, researchers suggested that culture Malaysian culture can be preserved through the street arts project.